2013
DOI: 10.1016/j.amjsurg.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of morning report by acute care surgery teams: results from a qualitative study

Abstract: Background The rigor of hand-offs is increasingly scrutinized in the era of shift-based patient care. Acute Care Surgery (ACS) embraced such a model of care; however, little is known about hand-offs in ACS programs. Methods We conducted 18 open-ended interviews with ACS leaders representing diverse geographic and practice settings. Two independent reviewers analyzed interviews using an inductive approach to elucidate themes regarding use of morning report (NVivo qualitative analysis software). Results 12/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…One comprehensive study by Pringle et al described how the strategic implementation of MR could lead to better outcomes, but how variability in team member attendance and lack of structured protocol can lead to under-utilization and suboptimal benefit of the model. [23] In our own institution, we wanted to address a previously identified issue of deficiencies in the patient hand-off systems, resulting in a gap in resident education in these necessary skills. [24] Studies have shown that MR is a valid format for resident education in efficient and effective patient handoffs.…”
Section: Discussionmentioning
confidence: 99%
“…One comprehensive study by Pringle et al described how the strategic implementation of MR could lead to better outcomes, but how variability in team member attendance and lack of structured protocol can lead to under-utilization and suboptimal benefit of the model. [23] In our own institution, we wanted to address a previously identified issue of deficiencies in the patient hand-off systems, resulting in a gap in resident education in these necessary skills. [24] Studies have shown that MR is a valid format for resident education in efficient and effective patient handoffs.…”
Section: Discussionmentioning
confidence: 99%
“…Still, there are some programs that have found innovative ways to ensure appropriate handovers within newly emerging ACS teams. 24 Similarly, while trauma quality improvement hinges upon comprehensive, prospective data collection, and the feasibility of such registries has been documented, 34,37 only a quarter of our fully implemented ACS programs had a registry.…”
Section: Discussionmentioning
confidence: 99%
“…Our qualitative study representing 18 teaching hospitals from different geographic and practice settings where an ACS model had been implemented found many variations in care delivery (e.g., patient cohorting, continuity clinics), workforce (e.g., critical care certification), resource allocation (e.g., dedicated EGS OR, in-house call), communication (e.g., face-to-face morning report), and data collection (e.g., registries). 24,25 These variations in our sample suggest that ACS is being variably implemented on a national scale. Therefore, it is impossible to tell if the benefits of ACS described at single centers that may have unique approaches to ACS would be generalizable across US hospitals.…”
Section: Introductionmentioning
confidence: 94%
“…Using exploratory data acquired from a qualitative study interviewing surgeons responsible for acute care surgery at 18 teaching hospitals (21, 22), we developed and tested a survey instrument in an iterative fashion creating an 8-page questionnaire that included items on resources allocated for EGS care at UHC hospitals. The survey was implemented using a hybrid postal and email methodology targeting a single senior surgeon at each hospital who would be able to respond to queries regarding the structures and processes for EGS care at their hospital as described previously (30).…”
Section: Methodsmentioning
confidence: 99%